2020
DOI: 10.1108/cms-03-2019-0086
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in a dynamic task: effects of goal orientation on stocks and flows performance

Abstract: Purpose This paper aims to investigate the effects of goal orientation on understanding the dynamics of stocks and flows (SF). Design/methodology/approach The authors use the well-established department store task as the experimental task to evaluate people’s understanding of SF and implement a survey to assess different goal orientation levels. Ordinary least square is used to test the effects of goal orientations on the SF performance. Findings The findings suggest that learning goal orientation is posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Rouwette et al [34], Aramburo et al [35], and Mohaghegh and Furlan [36] have summarized the key findings of the major works in this area based on characteristics of the system or task complexity: Delays, strength and types of feedback, exogenous change, use of heuristics or pattern matching mental models, systems thinking skills, and domain experience. In general, the presence of time delays as well as the length of delays tends to reduce performance [32,37], stronger feedback loops tend to reduce performance [32,[37][38][39][40][41][42], while exogenous changes have shown either reduced [40][41][42], improved [43], or no effect on performance [44]. Additionally, research has found consistent use of several decision making heuristics, particularly ones that employ pattern matching reasoning [30,36,[45][46][47][48][49][50][51][52][53][54], while others have found evidence of poor systems thinking skills to be pervasive throughout most individuals [55][56][57][58].…”
Section: Research On Decision-making In Relation To the Structures Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…Rouwette et al [34], Aramburo et al [35], and Mohaghegh and Furlan [36] have summarized the key findings of the major works in this area based on characteristics of the system or task complexity: Delays, strength and types of feedback, exogenous change, use of heuristics or pattern matching mental models, systems thinking skills, and domain experience. In general, the presence of time delays as well as the length of delays tends to reduce performance [32,37], stronger feedback loops tend to reduce performance [32,[37][38][39][40][41][42], while exogenous changes have shown either reduced [40][41][42], improved [43], or no effect on performance [44]. Additionally, research has found consistent use of several decision making heuristics, particularly ones that employ pattern matching reasoning [30,36,[45][46][47][48][49][50][51][52][53][54], while others have found evidence of poor systems thinking skills to be pervasive throughout most individuals [55][56][57][58].…”
Section: Research On Decision-making In Relation To the Structures Ofmentioning
confidence: 99%
“…• Types of feedback (e.g., numerical, graphical, or both) are known to influence behavior [32,42,[65][66][67].…”
Section: Dynamic Decision-making Characteristic Key Findings (With Somentioning
confidence: 99%
See 2 more Smart Citations